GANGGUANPOLITIKUANGTERHADAPPEMBANGUNAN - Purbayu Budi Santoso (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractWhen the election of regional chief hasn't been held yet directly. So money political practice is still easy to do. Recently, by the election of regional chief directly, money political practice assumed that is may be possible to do, by the way to give the materials to the party, which will nominate, even giving money and any helps to public figures who have many followers. With the more costs which given out by the regional chief that is nothing compares than his payment, so the actional fight againts the law can be done, by the public characters is paternalism, so money political practice can have large tripacts, which is in the end breaks the goals of development. Keywords: Money politic, Regional chief, Paternalism